3D heat transfer modeling and parametric study of a human body wearing thermal protective clothing exposed to flash fire. (17th April 2018) - Tian, Miao; Li, Jun
Summary: Understanding the heat transfer mechanism through a clothed man system in extreme environments is of great significance for human thermal protection. Three‐dimensional heat transfer models were developed based on the computational fluid dynamics considering a real‐shape human body in this study. The influences of air gap width, clothing thickness, and emissivity on the heat transfer within a dressed manikin exposed to flash fire were investigated. Simulated results indicated that the heat transfer in the air space was more complicated on the garment level than the fabric, because of the varying relative positions between different body segments and the heat source, as well as the ventilation openings. Increasing the fabric thickness was an effective method to reduce the transferred energy, which could remarkably lower the skin temperature. Decreasing both of the surface and backside emissivity from 0.9 to 0.3 could increase the protective performance, where surface emissivity reduction was recommended since the decrease of clothing temperature could minimize the risks of fabric degradation. The purpose of assuming the uniform air gap was to perform the parametric study, which was unrealistic indeed. The model with real clothing shape will be developed and investigated in the near future.